2020
DOI: 10.37201/req/066.2019
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of the special category antibiotics prescriptions in the Emergency Department of a third level urban Hospital

Abstract: Objective. The aim of the study was to analyze the adequacy of the special category antibiotics prescriptions in the Emergency Department (ED) of a third level urban Hospital. Material and methods. A random sample of 100 different patients who were started with a special category antibiotic along 2018 in the ED was selected. The research team reviewed the medical history of the emergency and admission episode. The independent factors associated with the degree of adequacy of the treatment were determined by lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…There is also evidence that an increase in the number of medications increases the probability of receiving a prescription for an antibiotic (Amaha et al, 2019). Finally, attacks classified as severe exposure were associated with a lower risk of inappropriate antibiotic use, a result that has also been shown in other clinical contexts (Muller et al, 2016; Osorio et al, 2020; Stuart et al, 2020). Muller et al (2016) and Osorio et al (2020) found that antibiotic prescriptions were adequate, especially when used for severe infections.…”
Section: Discussionsupporting
confidence: 72%
“…There is also evidence that an increase in the number of medications increases the probability of receiving a prescription for an antibiotic (Amaha et al, 2019). Finally, attacks classified as severe exposure were associated with a lower risk of inappropriate antibiotic use, a result that has also been shown in other clinical contexts (Muller et al, 2016; Osorio et al, 2020; Stuart et al, 2020). Muller et al (2016) and Osorio et al (2020) found that antibiotic prescriptions were adequate, especially when used for severe infections.…”
Section: Discussionsupporting
confidence: 72%
“…Con los hallazgos de este estudio se pueden llevar a cabo intervenciones particulares para cada institución; para ello, es importante identificar los factores que se asocian a una prescripción adecuada 20 , que incluyan medidas tales como la identificación de pacientes que más se beneficiarían con el tratamiento 21 , la realización de capacitaciones 22 , definición de antimicrobianos a restringir 5,22 , implementación de guías de diagnóstico 22 y de prescripción 23 , su seguimiento 22,23 y adherencia 24 , seguimiento farmacoterapéutico 22,23 y seguimiento a la resistencia 25 ,entre otras. De acuerdo a esto, se espera un efecto favorable, teniendo en cuenta que los programas de administración de antimicrobianos pueden ser bien aceptados por los médicos 26 .…”
Section: Discussionunclassified